A biomechanical study of neck strength and impact dynamics on head and neck injury parameters - Zaman, Rahid; Hossain, Mohammad Ibrahim; Raiyan, Ahmed Zubayer; Chowdhury, Shuvo; Jackson, Aaron; Koster, Arthur Thomas; Adnan, Ashfaq (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHead and neck injuries, including traumatic brain injuries (TBI), are a leading cause of disability and death worldwide. It affects millions of people worldwide, from automobiles to sports to military personnel. This study investigates the influence of impact locations, severities, and neck strength on head and neck injury parameters using a musculoskeletal head-neck model in OpenSim software.MethodsWe hypothesize that eccentric impacts, particularly those on the anterolateral side, increase GAMBIT and Neck Injury Criteria (NIC) due to elevated rotational accelerations, and that higher neck strength mitigates GAMBIT and NIC under these impacts. To test our hypotheses, we investigated a total of 63 cases in which seven impact locations (two from the anterior side, two from the posterior side, and three from lateral sides), three neck strengths (low, mid, high strength capacity), and three impact severities (low, moderate, and high) were explored. Seven output parameters were analyzed: linear and rotational accelerations, the Generalized Acceleration Model for Brain Injury Threshold (GAMBIT), neck force, neck moment, and Neck Injury Criteria (NIC) and neck muscle strain.ResultsResults reveal that anterolateral eccentric impacts pose the greatest risk, with rotational acceleration reaching 4,176 that is 4.75 times higher than anterior central impacts (879 rad/s2). GAMBIT values for moderate and high severity impacts are 1.44 and 1.54 times greater than low severity impacts, respectively. Head and neck injury parameters vary minimally (10) with neck strength.DiscussionIn summary, the severities and location of impacts had a significant role in GAMBIT and NIC, and the anterolateral eccentric impact had a higher probability of head and neck injury than the other six impact locations. These findings underscore the critical role of impact location and severity in injury risk and suggest helmet padding in lateral and anterolateral zones with energy-absorbing materials to reduce rotational acceleration.